2009
DOI: 10.1080/09273970903126543
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Outcome of Blunt Ocular Trauma: Rupture of Three Muscles

Abstract: In suspected extraocular muscle ruptures, orbital imaging methods and surgical exploration should be considered promptly. MRI may be mandatory to demonstrate the severed muscles in cases with persistent diplopia and normal CT. Prognosis is usually better in patients having partial extraocular muscle damage and treatment options should be evaluated on patient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In previous reports, both CT and magnetic resonance imaging (MRI) have been useful for preoperatively evaluating lacerated muscles. [2][3][4][5][6][7] In the current case, we were able to find the posterior portion of the lacerated medical rectus muscle with the aid of preoperative CT and repair it. MRI may be more useful for characterizing the shape of a muscle than CT.…”
Section: Discussionmentioning
confidence: 71%
“…In previous reports, both CT and magnetic resonance imaging (MRI) have been useful for preoperatively evaluating lacerated muscles. [2][3][4][5][6][7] In the current case, we were able to find the posterior portion of the lacerated medical rectus muscle with the aid of preoperative CT and repair it. MRI may be more useful for characterizing the shape of a muscle than CT.…”
Section: Discussionmentioning
confidence: 71%
“…There are few reports on the rupture of extraocular muscles [4], [5], [6], [7]. Rupture of the inferior rectus has been reported in three studies [5], [7].…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of the inferior rectus has been reported in three studies [5], [7]. Harish et al reported rupture of the superior oblique [4], while Sari et al reported the rupture of three rectus muscles in blunt trauma [5]. …”
Section: Discussionmentioning
confidence: 99%
“…All 6 extraocular muscles might be involved in these conditions. 5 , 23 27 However, the most commonly involved muscles are the medial and inferior rectus muscles, as these muscles are nearest to the corneoscleral limbus. In addition, Bell's phenomenon, a protective upward and outward movement of the eye, increases the exposure of these 2 muscles.…”
Section: Discussionmentioning
confidence: 99%